Establishment, Long‐Term Maintenance, and Characterization of Primary Liver Cells from Astyanax mexicanus. Issue 4 (17th April 2023) - Rajendran, Naresh; Deng, Fengyan; Wang, Yan; Kenzior, Olga; Krishnan, Jaya; Biswas, Tathagata; Parmely, Tari; Rohner, Nicolas; Zhao, Chongbei
Abstract: The tetra fish species Astyanax mexicanus comprises two morphotypes: cavefish that live in caves and surface fish that inhabit rivers and lakes. Because cavefish have adapted to the nutrient‐poor conditions in their habitat whereas the surface fish populations can be used as a proxy for the ancestral condition, this species has become a powerful model system for understanding genetic variation underlying metabolic adaptation. The liver plays a critical role in glucose and fat metabolism in the body and hence is an important tissue for studying altered metabolism in health and disease. Cavefish morphs of A. mexicanus have been shown to develop fatty livers and exhibit massive differences in gene expression and chromatin architecture. Primary cell lines from various tissues have become invaluable tools for biochemical, toxicology, and cell biology experiments, as well as genetic and genomic analyses. To enhance the utility of the model system by enabling an expanded set of biochemical and in vitro experiments, we developed protocols for the isolation and maintenance of primary liver cells from A. mexicanus surface fish and cavefish. We also describe methods that can be used for primary cell characterization, including cloning, characterization of cell growth pattern, and lentivirus transduction. © 2023 Wiley Periodicals LLC. Basic Protocol 1 : Primary culture of liver cells Support Protocol 1 : Maintenance of A. mexicanus primary liver cells Support Protocol 2 : Banking of A. mexicanus primary liver cells Support Protocol 3 : Recovery of A. mexicanus primary liver cells Support Protocol 4 : Primary liver cell cloning Support Protocol 5 : Characterization of A. mexicanus primary liver cell growth pattern Basic Protocol 2 : Lentiviral transduction of A. mexicanus primary liver cells